The production of nanoliposomal system containing Ducrosia anethifolia (DC.) Boiss essential oil made by sonication and filtration methods - Shahrzad Salari; Mehrdad Shamsaddini (Institue of Medicinal Plants, ACECR, 2020)
Background: Ducrosia anethifolia (DC.) Boiss is native to Iran and its essential oil has cytotoxic effects. Objective: Herbal Essences have limited application due to instability. In this research, nanoliposome containing Ducrosia essential oil has been studied for abundance and size distribution to enhance the essential oil stability for use in drug delivery systems. Methods: Essential oil was prepared and GC-MS were used to identify the extracted compounds. Thin-film hydration method was then used to create small liposome loaded with the extract. Nano-liposomes were made by sonication and filtration methods with molar ratios 7:3, 3:2 and ratios of 3:1 V/V Essential oil to lipid phase. Results: The results showed that size of nanoparticles made by sonication method with molar ratios of 3:2 was 39.49 to 354.4 nm with 80.7 to 19.3 % abundance and PDI of 0.856 Encapsulation Efficiency 38% and  size of liposomes prepared using filtration method was 269.8 nm with 100% abundance and PDI of 0.507 with Encapsulation Efficiency 34% and results of nanoliposomes made by sonication with molar ratios of 7:3 and  ratios of 3:1 was 224.4 to 5330 nm with 93 to 7 % abundance and PDI of 0.229 with Encapsulation Efficiency 46%. The size of liposomes prepared using filtration was 358.9 nm with 100% abundance and PDI of 0.286 with Encapsulation Efficiency 43.5%. Conclusion: It is important to note that the nanoliposomes produced by the sonication are smaller than filtration for use in the liposomal nanoscale system and Encapsulation Efficiency nanoliposomes made by molar ratios 7:3 was more than 3:2 molar ratios.